Digital Game Design for Older Adults : A Conceptual Framework - Nurul Farinah, Mohsin; Suriati Khartini, Jali; Sylvester, Arnab; Mohamad Imran, Bandan; Nurfauza, Jali; Amelia Jati, Robert Jupit (Semarak Ilmu Publishing, 2024)
The digital revolution, particularly digital games, can potentially improve older adults' lives. However, the commercialised digital games on the market are not designed specifically to help this demographic cope with the adverse effects of ageing. There are no specific guidelines or frameworks that consider the andragogy principles. We aimed to address our research question: How can older adults’ game experience influence design consideration? and discusses a framework that could aid the design and development of digital games focusing on older adults and their gaming experience. Mixed-method approach is used in this study, consisting of four stages in the research design. This article introduces and discusses the purpose, design, play and experience (PDPE) framework which has informed the development of a game prototype that was used to validate the framework by investigating older adults’ experiences.